2019
DOI: 10.1111/anu.13000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dietary creatine and guanidinoacetic acid supplementation in juvenile red drumSciaenops ocellatus

Abstract: Two separate comparative feeding trials were conducted to evaluate if supplemental dietary guanidinoacetic acid (GDA), either singly or in combination with creatine, could enhance growth performance of red drum. The basal diet for both trials was formulated with practical ingredients but was not supplemented with creatine or GDA. For the experimental diets, creatine (0 or 20 g/kg) and GDA (0, 5 or 10 g/kg) were added to the basal diet in a 2 × 3 factorial arrangement for trial 1. Another 2 × 3 experimental des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
(15 reference statements)
3
9
1
Order By: Relevance
“…In our study, the effect of GAA on the marbling score and IMF was the same, with a trend toward improvement. GAA supplementation increased the IMF content in LT of Tibetan pigs by 75.12%, which was similar to previous studies showing that the IMF content was significantly increased in pigs and fish fed GAA ( 10 , 24 ). In addition, GAA did not alter the protein nutrition of Tibetan pigs, which was consistent with previous studies ( 5 , 25 ) claiming that GAA had no significant effect on muscle chemical composition.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the effect of GAA on the marbling score and IMF was the same, with a trend toward improvement. GAA supplementation increased the IMF content in LT of Tibetan pigs by 75.12%, which was similar to previous studies showing that the IMF content was significantly increased in pigs and fish fed GAA ( 10 , 24 ). In addition, GAA did not alter the protein nutrition of Tibetan pigs, which was consistent with previous studies ( 5 , 25 ) claiming that GAA had no significant effect on muscle chemical composition.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study showed that fat accumulation increased when tissue creatine decreased in GC upon faba bean consumption [29], suggesting a negative correlation between fat accumulation and creatine. However, our results are not consistent with the red drum carnivorous fish [12,13]. The difference between these two results may be (1) fish specific; GC are herbivorous fish that may not tolerate higher levels of creatine in the body;…”
Section: Discussioncontrasting
confidence: 87%
“…A study in gilthead seabream (Sparus aurata) shows that dietary creatine produces no improvements in muscle performance as it does in mammals but alters physiological protein expression (such as in lipid metabolism, metabolic pathways, and in cell processes) in the liver [11]. Interestingly, appropriate amounts of creatine in the diet improved growth and feeding efficiency of carnivorous red drum (Sciaenops ocellatus) [12,13], whereas there were no obvious differences in regard to the lipid accumulation in the whole body or muscle in this fish species. Dietary creatine can reduce the serum triglyceride (TG) and total cholesterol (TC) contents in red tilapia (Oreochromis sp.)…”
Section: Introductionmentioning
confidence: 99%
“…. This was consistent with studies conducted on Sciaenops ocellatus, Sparus aurata, and pigs(James et al 2002;Schaffer et al 2009;Stites et al 2020), but some other studies found that creatine supplementation improved the growth performance of red Betaine supplementation can alleviate the negative impacts of HCD, including improving the growth parameters and liver condition in M. amblycephala(Xu et al 2017). Creatine supplementation can also improve the liver damage caused by a high-fat diet in mice (da Silva et al 2017…”
supporting
confidence: 85%